T-cell receptor and carbamazepine-induced Stevens–Johnson syndrome and toxic epidermal necrolysis: understanding a hypersensitivity reaction. (July 2012) - Ko, Tai-Ming; Chen, Yuan-Tsong
Ample evidence exists to support the view that drug hypersensitivity is mediated by adaptive immunity, which involves MHC-restricted drug presentation, activation and clonal expansion of T cells. The specific MHC molecules implicated in hypersensitivity have been identified; for example, HLA-B*5701 in abacavir-induced drug hypersensitivity and HLA-B*1502 in carbamazepine-induced Stevens–Johnson syndrome. However, little is known about the role of drug-specific T cells and their T-cell receptors (TCRs) in the pathogenesis of drug hypersensitivity. Using the combination of a strong HLA-B*1502 predisposition in carbamazepine-induced Stevens–Johnson syndrome and applying global analysis of the TCR repertoire, restricted and common TCR usage in the development of severe drug hypersensitivity have recently been documented. This article reviews recent advances in the understanding of the pathogenic role of drug-specific T cells and their TCRs in the development of drug hypersensitivity and provides an analysis of their potential clinical implications.